2001
DOI: 10.1002/1521-4109(200112)13:18<1485::aid-elan1485>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Voltammetric Method to Follow the Hydrolytic Degradation of Nitrendipine and Nisoldipine

Abstract: The development and application of a differential pulse voltammetric procedure for the hydrolytic degradation kinetic study of two wellknown 1,4-dihydropyridine type drugs, nitrendipine and nisoldipine are presented. The DPV procedure exhibited an adequate selectivity, repeatability and reproducibility with CV lower than 2%. The recoveries were higher than 98% with CV of 1.63% and 1.87% for nitrendipine and nisoldipine, respectively. Hydrolysis of each drug was carried out in ethanol=Britton-Robinson buffer (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…On the other hand, the aromatization of the 1,4-dihydropyridine ring to the corresponding pyridine derivative constitutes the most important in vivo reaction to terminate the pharmacological effect in the current clinically used drugs. 37 Finally, on the basis of findings presented here and other previous studies 27,29,31,33,34 Scheme 2 concerning the oxidation mechanism in an aprotic medium can be postulated. This mechanism is supported by two experimental facts: ͑i͒ the generation of the neutral dihydropyridyl radical intermediates C-centered was demonstrated by the trapping of these species with PBN and their characteristic spin adducts were determined by the ESR technique for the three compounds and ͑ii͒ the pyridine derivatives were identified by GC-MS as the final oxidation products in the aprotic medium.…”
Section: F26supporting
confidence: 59%
See 1 more Smart Citation
“…On the other hand, the aromatization of the 1,4-dihydropyridine ring to the corresponding pyridine derivative constitutes the most important in vivo reaction to terminate the pharmacological effect in the current clinically used drugs. 37 Finally, on the basis of findings presented here and other previous studies 27,29,31,33,34 Scheme 2 concerning the oxidation mechanism in an aprotic medium can be postulated. This mechanism is supported by two experimental facts: ͑i͒ the generation of the neutral dihydropyridyl radical intermediates C-centered was demonstrated by the trapping of these species with PBN and their characteristic spin adducts were determined by the ESR technique for the three compounds and ͑ii͒ the pyridine derivatives were identified by GC-MS as the final oxidation products in the aprotic medium.…”
Section: F26supporting
confidence: 59%
“…21,22 Investigations dealing with the electrochemical oxidation of some 1,4-DHPs have previously been performed in both nonaqueous [23][24][25][26] and aqueous media. [27][28][29] We recently reported 30 the synthesis and electrochemical oxidation of some new 3,5-͑substituted͒-4-͑5Ј-nitro-2Ј-furyl͒-1,4-DHP derivatives in a protic medium. In that paper, a detailed study in aqueous medium on the electro-oxidation of these compounds is reported.…”
mentioning
confidence: 99%